Proceedings of the International Conference of the Groupe d'etude des Ressources Maritimes on Small-scale Fisheries and Economic Development and of the Third Biennial Conference of the International Institute of Fisheries Economics and Trade... (Groupe de etude des ressources maritimes QuebecCA, 1987)
Contains papers on several aspects of the following broad fishery related headings: marketing and trade; fleets and vessels; investment; freshwater-aquaculture; fishermen; management; fishery outlook of selected countries; training and development.
Text in English, Spanish, French.Includes bibliographies